Digital Economy, Artificial Intellect, Industry 5.0: Today’s Challenges - N. V. Barinova; V. R. Barinov (Вестник Российского экономического университета имени Г. В. Плеханова)
The present day development of digital economy is closely connected with achievements in the field of artificial intellect. The article analyzes key approaches to investigation of the terms ‘strong artificial intellect’ and ‘weak artificial intellect’ that were introduced to academic literature by different researchers. The principle content of the article deals with problems of artificial intellect in Russian and overseas economy. The authors demonstrate the key lines of using artificial intellect that are necessary for today’s life. These lines include medicine, navigation, agriculture, retail, marketing, linguistics, etc. They provide arguments showing that artificial intellect can lead to a new stage of developing man-machine interaction. However, the overall application of artificial intellect systems and neural nets can be hazardous. The article identifies key threats that could face mankind in case of mass introduction of artificial intellect in all spheres of life. Academic works dealing with this problem were analyzed, Russian and overseas organizations studying potential threats of artificial intellect were named. The principle conclusion shown in the research gives evidence that the scale and degree of using artificial intellect should be limited by legal and moral standards of human life to avoid serious consequences. And finally, conclusions were made about trends of developing artificial intellect and Industry 5.0 in the era of digitalization